0637 Alternative Scoring Paradigms Of Rest-activity Consolidation (rac) In Moderate To Severe Traumatic Brain Injury (tbi) During Inpatient Rehabilitation. (12th April 2019) - Richardson, Risa; Silva, Marc; Calero, Karel; Zeitzer, Jamie
Abstract: Introduction: Objective actigraphy is a valid proxy of the criterion standard of sleep (EEG-based polysomnography) in TBI. TBI morbidity precludes guideline-recommended scoring. RAC has been associated with cognitive status during acute care. No study has examined RAC during rehabilitation or compared methods for determining abnormality. This study compared two aggregate measures of RAC abnormality on outcomes to operationalize an evidence-based biomarker of circadian disruption and inform treatment. Methods: Consecutive VA TBI Model System participants from a single Polytrauma Center from 2013-2016 were examined (n=70, male (92%), middle age (median age=32), with severe injury (median GCS=6). Admissions received a minimum of 3 days of ACG (median=56 days post-TBI) and outcomes (PTA duration, Functional Independence Measurement/FIM, Disability Rating Scale/DRS). Daily RAC was computed using previously reported metrics (daytime activity/24-hour activity; daytime interval defined as 0600-2200). Two criteria for determining RAC normalcy were compared: mean RAC across three days (Mean Method) and presence of RAC<80% on any of the three days (Fluctuation Method). Results: Greater than 80% of the cohort showed normal RAC (≥80%) each day; however, the participants moved in and out of the normal/abnormal group across the three days. A greater proportion of the sample was abnormal using the Fluctuation Method (31%) compared to the Mean Method (19%). Across both methods, the abnormal and normal groups were comparable on time elapsed since injury to actigraphy assessment and injury severity indices (emergency department GCS, and time to follow commands). Participants with abnormal RAC using the Fluctuation Method had longer duration of PTA (p=.008) and worse outcomes on rehabilitation admission FIM (cognitive [p=.027], motor [p=.011]) and DRS (p=.037). Participants with abnormal RAC using the mean method only differed on the motor FIM (p=.011). Conclusion: A greater proportion of the sample had abnormal RAC when examining consistency across a 72-hour interval and had worse outcomes compared to mean RAC. Findings inform development of an objective biomarker of circadian disruption that informs a precision medicine approach to sleep management in TBI. Support (If Any): DVBIC